The Impetus of COVID-19 in Transforming Nursing Education Through Informatics (Quality Advancement in Nursing Education - Avancées en formation infirmière, 2022)
Background: National nursing organizations worldwide have called for the inclusion of digital tools in nursing curricula to prepare future nurses to use digital tools in their professional practice.Objective: This study explored the experiences of nursing faculty with respect to integrating digital tools in their teaching to support undergraduate student learning during the COVID-19 pandemic.Method: This study was a focused ethnography featuring semi-structured interviews, field notes, and artifacts. Data were analyzed concurrently with data collection, using thematic analysis. A total of 21 participants from nine undergraduate nursing programs in Western Canada were interviewed as part of a larger study. This paper focuses on the 12 participants who were interviewed during the COVID-19 pandemic.Results: This paper discusses four themes related to faculty experiences using digital tools to support student learning during the COVID-19 pandemic: a) the pandemic, b) enablers, c) challenges, and d) learners. Faculty quickly transitioned from in-person to remote and virtual teaching, changing how they engaged with digital tools. Faculty were responsive and collectively rose to the challenges they faced, which suggests their agility and willingness to embrace informatics.Conclusion: The pandemic created an impetus for nursing faculty to utilize more digital tools to sustain the continuity of education. Further support and resources are needed to increase faculty informatics capacity in a more systematic way.